Does the Great Canon of Andrew of Crete speak about the heresies and their combating? Brief Remarks - Prelipcean, Alexandru (Vox Patrum, 2018)
It is known that the fundamental work of Andrew of Crete, probably written in the early of the eighth century, is penitential one, indicating continuing human need for repentance. Beyond a systematic exposition of Holy Scripture and its models (negative and positive), the Great Canon calls for deep meditation about life and its transience. Even the Byzantine author herself testifies this fact, saying: “Where shall I begin to lament the deeds of my wretched life? How shall I begin, O Christ, to relieve my present tears? But as Thou art deeply compassionate, grant me forgiveness of sins” (Ode 1, 1). But can we speak in the text of the Great Canon about polemical intentions against heresies? Can we find passages to develop the theological opinion against various heresies arisen within the Church over the eight centuries? If so, which ones and what heresy combat? This essay is at stake we want to present it.